Makeup sebagai Bentuk Ekspresi dan Kepercayaan Diri - Nayla Saskia Rahma; Fathiya Lensi Prastiwi; Alviatur Rosadah; Waqofa Adinda Almaaidah; Nabila Naufa Putri; Anik Maghfiroh (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The phenomenon of makeup use among Indonesian women is growing as part of the construction of social and cultural identity. This study aims to explore the meaning of makeup use as a form of self-expression and its relationship to women's self-confidence within the Indonesian socio-cultural context. This study used a descriptive qualitative approach with data collection through an online questionnaire. Respondents in this study were teenagers and university students who had experience using makeup. Data were analyzed by grouping respondents' answers into main themes, such as self-expression, reasons for using makeup, and its influence on self-confidence. The results show that the majority of respondents use makeup both routinely and in specific situations, particularly in social activities. Makeup is understood not only as a means of enhancing appearance but also as a medium of self-expression that represents personal identity and character. Most respondents felt more confident after using makeup, especially in situations that require social interaction. However, it was also found that self-confidence does not depend entirely on the use of makeup. These findings enrich the study of women's identity construction in Indonesian popular culture.